State sanctions policy: Historical and legal review - Aleksey A. Malinovsky; Elena N. Trikoz (RUDN Journal of Law)
The sanctions practice of modern states is introducing increasingly sophisticated methods of political, economic, trade, organizational and legal restrictions, which constitute an institutional strategy of multi-vector impact on the "target state". A special legal institution of counter-sanction measures and instruments of the corresponding sanctions policy is becoming a necessary part of the mechanism for implementing external functions of the defending sovereign state. The multiplicity of sanctions restrictions and the emergence of hybrid restrictive measures give special significance to the development of effective sanctions legislation at the level of individual states and international organizations. The purpose of this article is to study the normative legal foundations of the sanctions policy of states in their historical retrospective. This article applies comparative legal methodology, formal legal analysis and historical and theoretical description of the formation of classical restrictive and punitive sanctions. The final conclusions show that the sanctions strategy of states is gradually being transformed towards expanding the list of methods for its practical implementation (in the form of sectoral sanctions, freezing of assets, sanctions lists, tracking trade with the enemy, control of smuggling and shadow fleets, extraterritorial influence on neutral countries, “controlled technological backwardness”, application of “moral embargo”, etc.). The authors summarize that the so-called “sanctions war” has become a natural result of the introduction of counter-sanctions in practice as retaliatory measures of the state and the international principle of reciprocity, which means the right to equality and mutual respect between states.